Religious Pluralism: A Critical Review - Saad, Eva Sadia (Philosophy and Progress, 2012)
One of the most commonly used concepts in contemporary Religious Studies is Religious Pluralism. As the term indicates it is closely related to religious tolerance and minority rights. In recent times it has gained considerable importance because of the increasing diversity of religions in various communities of the world and also because of increasing restlessness in to days world due to religious conflict. The long tradition of philosophical thinking to strive and achieve a world community of mutual trust and harmony is another reason for sustained investigation in this area. There are, however, various thoughts and ideas which point towards the common goal of religious pluralism; but more often than not such efforts are jeopardized by a variety of different and contradictory theories and hypotheses which makes consensus difficult if not impossible. In this paper an attempt has been made to enumerate all the different view points particularly those related to Christianity and Islam. It will also attempt to analyze religions in their different roles and manifestations. In this sense, we hope, we can identify the different aspects of religion so as to find out the nature of their convergence and divergence. DOI: http://dx.doi.org/10.3329/pp.v50i1-2.11924 Philosophy and Progress: Vols. XLIX-L, January-June, July-December, 2011, p.89-108